CLINICAL AND LABORATORY FEATURES OF ENDOGENOUS INTOXICATION SYNDROME IN CHILDREN UNDER 3 YEARS WITH PNEUMONIA - R.M. ABDURAKHIMOV; A. VOKHIDOV (Avicenna Tajik State Medical University, 2020)
Objective: To study the clinical features of the course and the dynamics of some haematological indices in endogenous intoxication syndrome in children under 3 years of age suffering from pneumonia. Methods: There were 80 children under surveillance, of which 60 were pneumonia patients (main group), and 20 healthy children (control group). Laboratory survey included determining levels of leukocyte index of intoxication (LII), lactic and uric acids. The respiratory failure (RF) I is noted in 51.6%, RF II in 34.2% and RF III in 14.2% of cases. Results: Clinically and radiologically, 60.5% of children were diagnosed with bilateral processes in lungs, and in 39.5% the unilateral process. Signs of endogenous intoxication were: hyperhidrosis (59.4%), acrocyanosis (46.6%), perioral cyanosis (55.5%), mottled skin integument (49.2%), pronounced subcutaneous venous network (48.2%). The LII rate in the acute period had a strong tendency towards an increase of up to 5 days, with a gradual reduction to normal reference values by the end of the first week. It was found that high levels of lactic and uric acids were closely correlated with hypoxia. For example, in RF I, II and III levels of lactic acid were 1.3±0.1, 1.9±0.2 and 2.61±0.25 respectively. Children with RF III have degrees of lactic acid concentration that was statistically significant (p<0.001) higher than in the control group. Conclusion: Lactic and uric acid levels depend on the degree of RF and can indicate the severity of endogenous intoxication syndrome. The reduction of LII indices below 3.0 by the end of the first week of the disease, maybe a sign of a favorable outcome.